2014
DOI: 10.1515/zpch-2014-0586
|View full text |Cite
|
Sign up to set email alerts
|

The Internal Network Dynamics of Poly(NIPAM) Based Copolymer Micro- and Macrogels: A Comparative Neutron Spin-Echo Study

Abstract: Microgels are generally synthesised above the lower critical solution temperature (LCST) of the used polymer (poly(N-isopropyl-acrylamide)(PNIPAM) in the present case) and there is evidence that, due to the "bad" solvent conditions and due to the differences in reactivity between the monomers and the crosslinker, an inhomogeneous crosslinker distribution in the network is created. In contrast, macrogels are statistically crosslinked, because they are polymerised below the LCST (good solvent conditions). With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The validity of this assumption was already demonstrated in NSE experiments on PNIPAM microgels. 23,24 As discussed above, the chosen high volume fraction of microgel particles allows to neglect the contribution of translational diffusion. Hence, the measured normalized intermediate scattering functions should completely decay to zero and S(Q,τ NSE )/S(Q,0) can be fitted by…”
Section: Neutron Spin Echo Spectroscopy In Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The validity of this assumption was already demonstrated in NSE experiments on PNIPAM microgels. 23,24 As discussed above, the chosen high volume fraction of microgel particles allows to neglect the contribution of translational diffusion. Hence, the measured normalized intermediate scattering functions should completely decay to zero and S(Q,τ NSE )/S(Q,0) can be fitted by…”
Section: Neutron Spin Echo Spectroscopy In Transmissionmentioning
confidence: 99%
“…23 A comparison of chemically identical PNIPAM micro-and macrogels revealed that the cooperative diffusion and the accociated dynamic correlation length are very similar. 24 Recent studies explored the influence of the cononsolvency on the dynamics. 25,26 Beside the cooperative diffusion, also Zimm-type dynamics at higher values of the momentum transfer Q were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, measurements of the polymer dynamics inside microgels can reveal additional information. As reported in the literature, neutron spin echo spectroscopy (NSE) is a suitable scattering technique to explore the dynamics in microgel dispersions and inside adsorbed microgel particles. We employed neutron spin echo spectroscopy under grazing incidence (GINSES) to probe the internal dynamics of adsorbed PNIPAM-based microgels with comparatively high amounts of cross-linker (10 mol %). Microgel particles were prepared with a conventional batch method (“batch microgels”) and a continuous monomer feeding method (“feeding microgels”).…”
Section: Introductionmentioning
confidence: 99%
“…It has proved to be an excellent tool for investigating dynamics in polymer gels. [40][41][42][43][44][45] It has been a fertile source of important new insights into polymer melt-silica nanocomposite systems, 46,47 but to our knowledge, no investigation of PNIPA hydrogel composite systems using NSE has yet been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%